THE BOOK OF BUSTAN AL-SALATIN BY NUR AL-DIN AL-RANIRI AS HISTORICAL TEXT: THE STRUCTURE AND PURPOSE OF WRITING - Hamzah, Norhayati; Mohd Noor, Arba'iyah; Denisova, Tatiana (Journal of Al-Tamaddun, 2014)
The arrival of Islam in the Malay World has resulted in the beginning of intellectualism and rationalism among Malays especially in the 17th century Aceh (1511-1650). One of the prominent scholars of Aceh is Nuruddin Muhammad bin Ali bin Hasanji bin Muhammad Hamid al-Raniri al-Quraisyi al-Shafii, known as Nuruddin al-Raniri (d. 1658). Al-Raniri was an ulama, sufi, jurist and man of letters as well as a historian during the rule of Sultan Iskandar Thani (1636-1641). As a historian, al-Raniri contributes greatly to the development of a new form of Malay historical writing through his concept of universal history and the concept of Islamic history that are manifested in his work on history entitled Bustan al-Salatin fi Dhikr al-Awwalin wa al-Akhirin (The Garden of the Kings on the Recollection of the Past and Present). Therefore, this article attempts to accentuate Bustan al-Salatin as a book of Islamic history through the discussion about the structure of Bustan al-Salatin and al-Raniris purpose of writing Bustan.